DEVELOPMENT OF AN EVALUATION METHOD FOR RIVER ENVIRONMENT - H. Araki; K. Koga; Y. Nishi; Y. Kajiya; S. Imae; S. Kimura; K. Hirano; M. Sakanashi; S. Toyosaki; H. Fukuyama (International Association of Lowland Technology, 1999)
Assessment in planning and designing process is necessary especially for nature-oriented river. The main purpose of this study is to develop an assessment method for river environment. At a workshop composed of experts on river environment, a viewpoint to identify characteristics of watershed and/or river environment was added to viewpoints of the River Council in Japan. Furthermore, the new concept of